1986
DOI: 10.1136/gut.27.4.433
|View full text |Cite
|
Sign up to set email alerts
|

Increased gastric secretory capacity in smokers without gastrointestinal lesions.

Abstract: SUMMARYThe relationship between smoking and gastric secretory capacity was studied in 201 25-40 year old healthy subjects with normal laboratory data and no gastrointestinal lesions. Basal acid output (BAO) and peak acid output (PAO) were determined in all, and basal and stimulated pepsin outputs were measured in 85 participants. The accuracy of the patients' statements was checked by urinary nicotine assay. Basal acid output and PAO were significantly higher in male smokers (n=55) than in male non-smokers (n=… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…When the pepsin output in gastric juice was measured, smokers had a higher pepsin output than non-smokers. This was confirmed both in patients with duodenal ulcer (Boyd et al, 1983) and in healthy subjects (Massarrat et al, 1986). Another study among patients with duodenal ulcer confirmed that the levels of serum pepsinogen I were higher in smokers than in non-smokers (Lanas et al, 1990).…”
Section: Resultsmentioning
confidence: 69%
“…When the pepsin output in gastric juice was measured, smokers had a higher pepsin output than non-smokers. This was confirmed both in patients with duodenal ulcer (Boyd et al, 1983) and in healthy subjects (Massarrat et al, 1986). Another study among patients with duodenal ulcer confirmed that the levels of serum pepsinogen I were higher in smokers than in non-smokers (Lanas et al, 1990).…”
Section: Resultsmentioning
confidence: 69%
“…Cigarette smoking has multiple influences on the gastric mucosa, possibly including increased acid secretion (36) and increased bile reflux (37).…”
Section: Smoking and Peptic Ulcermentioning
confidence: 99%
“…Usual cigarette smoking may lead to both increased basal acid gastric secretion, and basal and stimulated pepsin outputs. 24 The effect of acute cigarette smoking on acid gastric secretion remained however uncertain: it was reported that one or two cigarettes smoked transiently decreased acid secretion stimulated by infusion of pentagastrin in volunteers, 25 while other authors did not report any significant effect of acute cigarette smoking on stimulated gastric acid secretion. 26 As concerns the effect of acute smoking on gastric emptying, conflicting results were also published.…”
Section: Discussionmentioning
confidence: 99%